Дьяволиада: повести, рассказы, фельетоны, очерки. 1919-1924 - Булгаков Михаил Афанасьевич (1995)
Экземпляры: (20181107) / Инвентарный номер: 27897 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 90 / ББК: 84(2Рос=Рус)6